Syntheses of chiral 1,8-cineole-metabolites and determination of their enantiomeric composition in human urine after ingestion of 1,8-cineole-containing capsules. - Schaffarczyk, Monika; Balaban, Teodor Silviu; Rychlik, Michael; Büttner, Andrea (ChemPlusChem, 2013)
The chiral metabolites in human urine were investigated after ingestion of a 1,8‐cineole (eucalyptol)‐containing entero‐coated capsule (Soledum). For identification of the various enantiomers the enantiomerically pure (−/+)‐α2‐hydroxy‐1,8‐cineole, (−/+)‐β2‐hydroxy‐1,8‐cineole, (−/+)‐9‐hydroxy‐1,8‐cineole, and (−/+)‐2‐oxo‐1,8‐cineole were prepared. To achieve this aim, after acetylation of the synthesized racemic 2‐ and 9‐hydroxy‐1,8‐cineoles, pig liver esterase‐ or yeast‐mediated hydrolysis provided the (−)‐alcohols with their antipodal (+)‐acetates with enantiomeric excess of 33–100 %. Dess–Martin periodinane oxidation of the alcohol (+)‐α2‐hydroxy‐1,8‐cineole, obtained by hydrolysis of the resolved acetate, provided the corresponding (+)‐2‐oxo‐1,8‐cineole, meanwhile the oxidation of (−)‐α2‐hydroxy‐1,8‐cineole gave (−)‐2‐oxo‐1,8‐cineole. Using these standards seven metabolites (+/−)‐α2‐hydroxy‐1,8‐cineole, (+/−)‐β2‐hydroxy‐1,8‐cineole, (+/−)‐α3‐hydroxycineole, (+/−)‐3‐oxo‐1,8‐cineole, 4‐hydroxy‐1,8‐cineole, 7‐hydroxy‐1,8‐cineole, and (+/−)‐9‐hydroxy‐1,8‐cineole, all liberated from their glucuronides, were identified in urine by GC‐MS on a chiral stationary phase after consumption of 100 mg of 1,8‐cineole. Metabolite screening using 2H3‐1,8‐cineol as the internal standard revealed (+/−)‐α2‐hydroxy‐1,8‐cineole as the predominant metabolite followed by (+/−)‐9‐hydroxy‐1,8‐cineole. Furthermore, the results showed that one enantiomer is always formed preferentially.<br